Traumatic Sinus of Valsalva Aneurysm Repaired by Partial David Operation - Seki, Hiroshi; Borger, Michael; Mohr, Friedrich; Misfeld, Martin (The Thoracic and Cardiovascular Surgeon Reports, 2014)
We report a case of chronic type A dissection and aneurysm of the sinus of Valsalva after a motor bike accident which remained undetected for 20 years. It was successfully treated with a modified valve-preserving technique. The noncoronary sinus formed a 4.5 × 5.0 cm large and heavily calcified aneurysm, compressing the right atrium and right coronary artery. The pathology was limited to the noncoronary sinus area and here was the annulus dilatated but the remaining sinuses and annulus and the cusps were intact. We have therefore performed a one-third or partial-David procedure with a satisfactory result.
Keywords: aortic disease; cardiovascular surgery; trauma